Initiation of the flexirubin biosynthesis in Chitinophaga pinensis. Issue 3 (28th January 2014) - Schöner, Tim A.; Fuchs, Sebastian W.; Schönau, Christian; Bode, Helge B.
Summary Bacteria from the Bacteroidetes phylum are known producers of the chemotaxonomic relevant flexirubins. These orange pigments comprise a non‐isoprenoid aryl‐polyene carboxylic acid esterified with a dialkylresorcinol. Herein, we report a gene cluster from Chitinophaga pinensis encoding the biosynthesis of the polyene moiety and the biochemical characterization of a tyrosine ammonia‐lyase and a 4‐coumarate‐CoA ligase responsible for the initiation of the polyene biosynthesis. Additionally, the flexirubin of C. pinensis was characterized by a combination of feeding experiments, high‐performance liquid chromatography tandem mass spectrometry and matrix‐assisted laser desorption/ionization mass spectrometry.